Covalent 2D Patterning, Local Electronic Structure and Polarization Switching of Graphene at the Nanometer Level. Issue 34 (1st May 2021) - Bao, Lipiao; Zhao, Baolin; Assebban, Mhamed; Halik, Marcus; Hauke, Frank; Hirsch, Andreas
Abstract: A very facile and efficient protocol for the covalent patterning and properties tuning of graphene is reported. Highly reactive fluorine radicals were added to confined regions of graphene directed by laser writing on graphene coated with 1‐fluoro‐3, 3‐dimethylbenziodoxole. This process allows for the realization of exquisite patterns on graphene with resolutions down to 200 nm. The degree of functionalization, ranging from the unfunctionalized graphene to extremely high functionalized graphene, can be precisely tuned by controlling the laser irradiation time. Subsequent substitution of the initially patterned fluorine atoms afforded an unprecedented graphene nanostructure bearing thiophene groups. This substitution led to a complete switch of both the electronic structure and the polarization within the patterned graphene regions. This approach paves the way towards the precise modulation of the structure and properties of nanostructured graphene. Abstract : Nanoscale patterning and tailoring of graphene was realized by a very facile and highly efficient approach, which includes a first‐step patterned fluorination with a very high degree of functionalization, realized by laser writing, and a subsequent nucleophilic substitution of the attached fluorine atoms with thiophene groups.